Effects of ballast water on the aquatic quality of the Port areas of Callao, Pisco, Paita and Salaverry, Peru - Orozco, Rita (2020)
The growth of the shipping industry in Peru and the expansion of the port area of ​​Callao, Pisco, Paita and Salaverry, allow the entry of large ships. In the years 2009-2010, the entry of invasive species through ballast water was reported in Callao. An assessment of the ballast water was carried out in the ships that arrived at the port of Callao in 2010 and 2012. The aquatic quality of the ports of Paita Salaverry, Callao and Pisco was also evaluated between 2011 and 2013. The results show that in ballast water coliform counts were low from <2 to 8 NMP / 100ml, the presence of Vibrio parahaemolyticus and V. vulnificus was recorded. The phytoplankton species such as Heterosigma akashivo and Skeletonema costatum sp were the most representative. The marine waters of the port areas had normal values of temperature <20 ° C and salinities > 35.1 ups, but the aquatic quality was affected by anthropogenic activities with high values of thermotolerant coliforms in Callao of 1.6x106 NMP / 100ml. Dominant phytoplankton species produce algal blooms Dictyocha fibula and Prorocentrum micans in Paita, Prorocentrum minimun, A. sanguineum in Salaverry in 2012, Heterosigma akashiwo and Akashiwo sanguinea, from Callao and in 2013a. In the port of Pisco, the most abundant species were Cochlodinium polikrykoides in 2011 and Alexandrium peruvianum in May 2012. Ballast water is transporting invasive alien species that can cause serious effects on the marine ecosystem, human health and the economy, for which should strengthen the monitoring of ports with greater maritime traffic.